First evaluation of fruit quality of some new and old sour cherry cultivars in Hungarian climatic condition - H. G. Davarynejad; J. Nyéki; T. Szabó; J. Tornyai; M. Soltész; Z. Aryanpooya; Z. Szabó (International Journal of Horticultural Science, 2009)
Indeed, in the last decade a large number of new sour cherry cultivars with new notable flavor characteristics have been released. There is no enough information related to qualitative characteristics which consistently segregated based on their predominant sensory characteristics. The present study carried out at tow consecutive years (2008 and 2009) and examined some qualitative characters which are the main importance in the specialty cherries trade, The main objective was to determine fruits quality of Érdi bőtermő, Oblacsinszka, Debreceni bőtermő, Csengődi, Pándy 279, Éva, Kántorjánosi, Újfehértói fürtös and Petri sour cherry cultivars. Changes observed in major characteristics such as fruit detachment force, width, length, weight, peduncle length, flesh firmness, brix, citric acid, Suger/acid ratio and pit weigh.While observed no change in flesh/pit ratio and Coordinate of colour (X*, y*, x*), hue angle and chroma value, in different years. In all measured factors, there was significant difference between selected cultivars of sour cherry fruit. Debreceni bőtermő showed higher values of fruit detachment force in 2008, while had the lover of fruit detachment force in 2009. Fruit firmness of “Érdi bőtermő” were monitored at lover value in both 2-year.